Quartzose pseudomorphs in Upper Proterozoic sediments of the Blovice Formation; Czech Republic - Skocek,V.; Vavrdova,M. (Journal of the Czech Geological Society, 1994)
Three types of quartzose pseudomorphs were detected in thin sections: rhombohedral crystals and their aggregates interpreted as silicified dolomite, elongated crystals filled with drusy quartz, and silicified lenses both considered to be replaced sulphates. Cleavage, according to 1011, visible due to the accumulation of impurities within quartz crystals, indicates replacement of the original dolomite via a fluid film. Molds after elongated crystals were filled by drusy quartz from solution whereas the microfabric of lenses points to a complicated genesis (precipitation, hydration and dehydration) and subsequent silicification in the solid state. Pseudomorphs indicate hypersaline water within the environment where, in addition to deposition of black shales, stromatolites also formed.